ANALISIS RELEVANSI SANKSI ADMINISTRATIF DALAM KASUS MALADMINISTRATIF: TINJAUAN TERHADAP PERATURAN PEMERINTAH NO. 94 TAHUN 2021 TENTANG DISIPLIN ASN - Pamungkas, Satria Aji; Parama, Hadid Raissa; Budiman, Nirina Aulia Putri; Nugroho, Fauzi Rahadian Adi; Hudzaifi, Hamzah; Khoirunnisaa, Kayla Syifa (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2025)
The application of administrative sanctions under Government Regulation No. 94 of 2021 aims to enhance the discipline of Civil Servants (Aparatur Sipil Negara – ASN) and prevent occurrences of maladministration. This study seeks to analyze the relevance of applying administrative sanctions in addressing cases of maladministration. The research employs a normative juridical approach, focusing on statutory regulations and related legal literature. The findings indicate that, although Government Regulation No. 94/2021 provides a clear and comprehensive legal framework, the main challenges lie in inconsistent implementation and ineffective supervision. The enforcement of administrative sanctions must be supported by strict oversight and an increased awareness of ethical standards among civil servants in order to effectively prevent violations. In conclusion, while administrative sanctions have the potential to improve ASN behavior, their implementation must be reinforced through education, training, and transparent supervision to achieve the intended objectives.